Formation of the New Policy of Innovative Development of Kazakhstan in the Context of Current Innovation Models - Dnishev, Farkhat; Alzhanova, Farida; Korgasbekov, Dastan (International Review of Management and Marketing, 2016)
The goal of current article is to research features of the new models of innovation development, justification of mechanisms and priorities of innovation development of Kazakhstan's economy based on new models of innovation. Due to the opportunities offered by globalization, it seems appropriate in the innovative strategy of Kazakhstan to focus on the rational combination of its own scientific- technological resources and external (foreign) sources of knowledge and technology. This strategy defines the coexistence of two approaches: one approach is associated with the development of the innovative capacity of the country, the other - with the development of absorption capacity. Therefore double-contour mechanism is appropriate for innovative development of the national economy. This refers to the open innovation model and the model of the triple helix. By taking into account characteristics of these models we create two contours of the mechanism of innovative development in Kazakhstan, which differ in accents arranged during the application of country's measures of innovation policy and innovation behavior of companies. Keywords: innovation, innovative development models, technology, technology transfer. JEL Classifications: O10, O11, O31.